Leadership Strategies of the Principal in Improving Teacher Professionalism at MI Ma'arif 1 Gesing - Farokhi, Muhamad; Muntaqo, Lutfan; Muntaqo, Rifqi; Firdaus, Firdaus; Vantika, Siti (Journal of Education Technology and Inovation, 2025)
Schools as educational institutions aim to prepare students for future life by developing their full potential through effective teaching and learning processes supported by adequate facilities, a conducive environment, and well-structured lesson planning. The implementation of instructional planning is influenced by several factors, particularly teacher performance as a central component of the educational process. This study aims to examine teacher performance, analyze the principal's strategies in enhancing teacher professionalism, and identify the challenges in improving teacher professionalism at MI Ma'arif 1 Gesing. The research employs a descriptive qualitative approach, utilizing in-depth interviews, participant observation, and document analysis as data collection techniques. The findings indicate that teacher professionalism is demonstrated through academic qualifications and certification status, as most teachers hold undergraduate degrees and teach in accordance with their areas of expertise, experience, and competencies. Furthermore, the institution implements the Ministry of Religious Affairs' curriculum, along with additional extracurricular programs. The primary challenge in enhancing teacher professionalism is addressing the rapid impact of globalization, which requires teachers to preserve and strengthen Islamic values while adapting to contemporary educational developments.